O-036 Embolization of cranial dural arteriovenous fistulas: a sydney experience. (23rd July 2017) - Johnson, C
Abstract : Introduction: Endovascular management of dural arteriovenous fistulas has become a mainstay of treatment. In particular, modern techniques with newer devices such as dual-lumen balloon catheters and non-adhesive liquid embolic agents has allowed greater fistula penetration and greater likelihood of complete fistula obliteration. However, the efficacy of such techniques and newer agents has not been quantified. To this aim, we performed a retrospective review of our endovascular management of cranial dural arteriovenous fistulas in the liquid embolic era. Materials and Methods: This retrospective case series reviewed patients from three large tertiary referral centers over the past six years, managed by a small core group of neurointerventional radiologists. Consecutive patients between 2008 and 2016, treated for both acute and elective presentations, for any Cognard grade were included. Medical records, in addition to imaging databases, patient correspondence and personal logbooks were used to analyze data on rates of occlusion, residual, recurrence and complications. Results: 96 patients were included, aged 1–91 years of age, with a median age of 64 years. 72 patients had a Cognard grade of IIA+B or higher, and over half of all cases were located in the cavernous sinus, transverse or sigmoid sinus, posterior fossa or tentorium. All but 2 patients had their fistula managed by endovascular embolization as the intention to treat, and in 83 cases the embolic agent used was exclusively a liquid embolic agent, of which Onyx predominated. Patients who had other adjuncts to treatment such as coils were also included. 86/96 (89.6%) patients had complete angiographic cure of the fistula, 8/96 (8.3%) had a residual fistula and 2/96 (2%) had a recurrence of the fistula on follow-up imaging. There were 8 complications amongst this cohort, including 6 cranial nerve deficits, one cerebral infarct, and one death. The remaining 88/96 (92%) patients had no procedural complications. Conclusion: We believe this is the largest published cohort of cranial dural arteriovenous fistulas to date compared to that reported in the literature in the liquid embolic era which appears to demonstrate excellent treatment effect and safety outcomes. We thus advocate for primary endovascular treatment under an experienced neurointerventional team, with liquid embolic agents in the first instance, over other modalities of treatment. Disclosures: C. Johnson: None.